2021
DOI: 10.1101/2021.02.17.21251921
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Are fast test results preferable to high test sensitivity in contact-tracing strategies?

Abstract: Across the world, countries are fighting to reduce the spread of COVID-19. The backbone of the response is a test-trace-isolate strategy, where suspected infected get tested and isolated and possible secondary cases get traced, tested and isolated. Because more accurate tests often take longer to analyze, and the benefits of contact tracing are strengthened by rapid diagnosis, there exists a trade-off in test sensitivity and test waiting time in test-trace-isolate strategies. Here we ask: How many false negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The Ag test sensitivity shall be interpreted in light of the low prevalence in the investigated population, as low prevalence in general challenges sensitivity of diagnostics test [ 13 ]. Furthermore, the lower sensitivity of the Ag test, as described in the introduction, does not affect the important value of the Ag test in screening as long as frequency of the testing is high [ 4 , 5 , 6 ]. Recommendations suggest that the rapid Ag test is useful as an epidemiologic and scalable screening and results in a valid COVID passport when testing is frequent, that is, every third day [ 4 , 5 , 6 ], thus, the Ag test even with a lower sensitivity is an acceptable screening tool taking into account the minimal invasive method of collecting the sample for analysis, the fast result time, and the lower costs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The Ag test sensitivity shall be interpreted in light of the low prevalence in the investigated population, as low prevalence in general challenges sensitivity of diagnostics test [ 13 ]. Furthermore, the lower sensitivity of the Ag test, as described in the introduction, does not affect the important value of the Ag test in screening as long as frequency of the testing is high [ 4 , 5 , 6 ]. Recommendations suggest that the rapid Ag test is useful as an epidemiologic and scalable screening and results in a valid COVID passport when testing is frequent, that is, every third day [ 4 , 5 , 6 ], thus, the Ag test even with a lower sensitivity is an acceptable screening tool taking into account the minimal invasive method of collecting the sample for analysis, the fast result time, and the lower costs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the lower sensitivity of the Ag test, as described in the introduction, does not affect the important value of the Ag test in screening as long as frequency of the testing is high [ 4 , 5 , 6 ]. Recommendations suggest that the rapid Ag test is useful as an epidemiologic and scalable screening and results in a valid COVID passport when testing is frequent, that is, every third day [ 4 , 5 , 6 ], thus, the Ag test even with a lower sensitivity is an acceptable screening tool taking into account the minimal invasive method of collecting the sample for analysis, the fast result time, and the lower costs. It has further been shown that individuals with a lower Ct value, and thus a high viral load, have been associated with a higher transmissibility of SARS‐CoV‐2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary goal of severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) testing is to reduce the spread of coronavirus disease 2019 (COVID-19) [ 1 , 2 ]. Due to the highly infectious nature of SARS-CoV-2, there is an urgent need for a fast turnaround of results to institute preventative measures such as the isolation of confirmed cases and contact tracing [ 1 , 3 ]. Currently, reverse transcription polymerase chain reaction (RT-PCR) tests are the gold standard for diagnosing COVID-19 [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%